Karakteristik Sensori Kopi Celup Dan Kopi Instan Varietas Robusta Dan Arabika - N Nurhayati (Politeknik Negeri Jember, 2017)
Coffee is one of the plantation commodities that contribute to the significant role for agricultural development in Indonesia. Indonesia has two main coffee varieties, namely Arabica coffee and Robusta coffee. The objectives of the study were characterization of physical properties and quality of sensory coffee dye and instant coffee. The materials used are Robusta coffee and Arabica coffee. Physical properties analyzed were total dissolved solids by using refractometer. Sensory quality was tested by a distinctive scoring method that included aroma, taste, viscosity and color parameters. The results showed that the highest total dissolved solids were Arabica dye (43,67) compared to Robusta coffee (42,80). Instant coffee has the strongest flavor, taste and viscosity characteristics compared to coffee dyes. A strong flavor quality is owned by Arabica instant coffee. The strongest steeping quality is owned by Robusta instant coffee. High filling (condensed) is owned by Arabica type instant coffee. The color of the dark sedan is owned by Arabica instant coffee and Robusta.Â Keywords : Dye Coffee, Instant Coffee, Arabika, Robusta, sensory.Â